2021
DOI: 10.33545/gynae.2021.v5.i4b.966
|View full text |Cite
|
Sign up to set email alerts
|

A prospective clinical study of ectopic pregnancy at a tertiary care hospital, Shillong, Meghalaya

Abstract: Background: Ectopic pregnancy is one of the commonest cause of acute abdominal emergencies in obstetric practise with a case fatality rate of 1-3 % in developing countries. Therefore, it is imperative to diagnose the unruptured ectopic pregnancy to prevent morbidity and mortality Materials and Methodology: This was a prospective observational study of 1 year with the sample size of 44 cases out of 976 newly diagnosed first trimester pregnancies. Results: The incidence was found to be 4.5 % with the majority of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
0
2
Order By: Relevance
“…2 Studies suggest rising trend in cases of ectopic pregnancy due to better and sensitive diagnosis facility. 3,11,12 In our study we found incidence rate of EP to be 22.9 per 1000 deliveries or 2.29 %, which is higher than the national incidence as well the incidence reported in north-eastern part of India. 11,13 But our finding was lower than study of Ranji GG et al 14 who reported occurrence of EP to be 2.81% where she included cases which were manage medically as well as surgically.…”
Section: Discussioncontrasting
confidence: 47%
See 1 more Smart Citation
“…2 Studies suggest rising trend in cases of ectopic pregnancy due to better and sensitive diagnosis facility. 3,11,12 In our study we found incidence rate of EP to be 22.9 per 1000 deliveries or 2.29 %, which is higher than the national incidence as well the incidence reported in north-eastern part of India. 11,13 But our finding was lower than study of Ranji GG et al 14 who reported occurrence of EP to be 2.81% where she included cases which were manage medically as well as surgically.…”
Section: Discussioncontrasting
confidence: 47%
“…3,11,12 In our study we found incidence rate of EP to be 22.9 per 1000 deliveries or 2.29 %, which is higher than the national incidence as well the incidence reported in north-eastern part of India. 11,13 But our finding was lower than study of Ranji GG et al 14 who reported occurrence of EP to be 2.81% where she included cases which were manage medically as well as surgically. However the mortality rate in this study was 1.2% which is comparable to national mortality rate of ≤ 3.5%.…”
Section: Discussioncontrasting
confidence: 47%